(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Synthesis of biodiesel from waste animal fat was the first step in this research. Biodiesel was made using a traditional chemical process called transesterification. In transesterification process pure fat was reacted with methanol in presence of KOH as catalyst. For every 100 ml of pure liquid fat 1 gram of KOH with 20ml of methanol was used for reaction at around 60oc temperature. Following the production of biodiesel, blends of biodiesel and neat diesel in various mixing ratios, such as AFME5 (95 % D+5 % BD), AFME10 (90 % D+10 % BD), and AFME20 (80 % D+20 % BD) were prepared for carrying out the performance and emission tests on four stroke single-cylinder diesel engine. The primary physico chemical properties such as Calorific value, density, kinematic viscosity and CFPP of fat-based biodiesel and its blends were determined prior to testing. All of the properties measured were found to be in agreement with ASTM requirements.